(untitled) - Amthor, Frank (New Jerse, 2016)
Content: the brain. Covering the most recent scientific discoveries and complemented with helpful diagrams and engaging anecdotes that help bring the information to life, this updated edition offers a compelling and plain-English look at how the brain and nervous system function.
Keywords: Neurosciences,Khoa học thần kinh; Popular works.,Công trình phổ biến.